2021
DOI: 10.1210/clinem/dgab645
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Cardiometabolic Risk Profile Among Nondiabetic American Young Adults: Insights From NHANES

Abstract: Background The burden of insulin resistance (IR) among young American adults has not been previously assessed. We evaluated the 1) prevalence and trends of IR and cardiometabolic risk factors and, 2) assessed the association between measures of adiposity and IR among adults aged 18-44 years without diabetes and preexisting cardiovascular disease. Methods Cross-sectional survey data from six consecutive National Health and Nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 82 publications
3
19
0
Order By: Relevance
“…Our study demonstrated that MQ was most associated with CVD risk factor accumulation compared with SMI and HGS, regardless of sex and age (Table 2B ). MQ was reported to be negatively associated with insulin resistance after adjusting for age, body fat, highly sensitive C-reactive protein levels, and physical activity level in adult obese women [ 47 ] and further that insulin resistance contributes to the development of atherosclerosis [ 48 , 49 ], findings that are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrated that MQ was most associated with CVD risk factor accumulation compared with SMI and HGS, regardless of sex and age (Table 2B ). MQ was reported to be negatively associated with insulin resistance after adjusting for age, body fat, highly sensitive C-reactive protein levels, and physical activity level in adult obese women [ 47 ] and further that insulin resistance contributes to the development of atherosclerosis [ 48 , 49 ], findings that are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, low HGS has been reported to be associated with coronary artery calci cation, CVD, and all-cause mortality [45][46][47] Our study demonstrated that MQ was most associated with the accumulation of CVD risk factors compared with SMI and HGS, regardless of sex and age (Table 2B). MQ was reported to be negatively associated with insulin resistance after adjusting for age, body fat, highly sensitive C-reactive protein levels, and physical activity level in adult obese women [48] and further that insulin resistance contributes to the development of atherosclerosis [49,50], ndings that are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The average self-reported duration of sleep per day was obtained from the sleep disorders questionnaire. Additionally, data on insurance status (yes/no), number of healthcare visits in the past year (none, 1 to 3, 4 or more), poverty income ratio (≥3.50, 1.30-3.49, <1.30), and educational status (≤12 years of education, some college education, and a college degree or higher) were used in this study [ 15 , 22 ].…”
Section: Methodsmentioning
confidence: 99%